Factors associated with the political orientation on Muslim pupils in the Madrasah, public and private elementary schools in Mindanao - Batara, Corazon M.
The research sample consisted of 493 pupils from Grades 2, 4 and 6 drawn from 33 classes in 10 schools and 27 Social Studies teachers from the cities of Zamboanga, Cotabato and Marawi. The fathers of private school pupils are better educated than those from the Madaris, or public schools. The political orientation of pupils significantly differ in the three types of schools with the public school pupils more politically knowledgeable and positively oriented towards the government and political authorities than those from the Madaris and the private schools.